Palynological Zonation of the Paleogene–Neogene Strata of the Kaikang Trough, Muglad Rift Basin, Republic of South Sudan - Abdelrahim, O.; bin Ismail, M.; Hunter, Aaron (Springer Singapore, 2015)
Five palynological zones are identified in this Cenozoic-through-Quaternary section based on quantitative specimen counts calculated as absolute abundance. These palynological zones are: K-VI (Paleocene), K-VII (Eocene–Early Oligocene), K-VIII (Late Oligocene-Early Miocene), K-IX (Late Miocene–Pliocene), and K-X (Quaternary).